2018
DOI: 10.1038/s41598-017-18678-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability and anisotropy of (FexNi1−x)2O under high pressure and implications in Earth’s and super-Earths’ core

Abstract: Oxygen is thought to be an important light element in Earth’s core but the amount of oxygen in Earth’s core remains elusive. In addition, iron-rich iron oxides are of great interest and significance in the field of geoscience and condensed matter physics. Here, static calculations based on density functional theory demonstrate that I4/mmm-Fe2O is dynamically and mechanically stable and becomes energetically favorable with respect to the assemblage of hcp-Fe and -FeO above 270 GPa, which indicates that I4/mmm-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
(58 reference statements)
1
13
0
1
Order By: Relevance
“…Concerning the stability of these phases in the inner core, Ozawa et al () find B2‐FeO to be favored over B1‐FeO above 240 GPa at 4000 K, thereby suggesting the B2 phase is stable in the inner core, and ab initio studies by Huang et al () propose I4/mmm ‐Fe 2 O is energetically favorable above 270 GPa. However, experimental equations of state are not presently available for B2‐FeO or I4/mmm ‐Fe 2 O.…”
Section: Extrapolation To Inner Core Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the stability of these phases in the inner core, Ozawa et al () find B2‐FeO to be favored over B1‐FeO above 240 GPa at 4000 K, thereby suggesting the B2 phase is stable in the inner core, and ab initio studies by Huang et al () propose I4/mmm ‐Fe 2 O is energetically favorable above 270 GPa. However, experimental equations of state are not presently available for B2‐FeO or I4/mmm ‐Fe 2 O.…”
Section: Extrapolation To Inner Core Conditionsmentioning
confidence: 99%
“…The uncertainties on density, adiabatic bulk modulus, and bulk sound speed at high temperature for FeO, FeS 2 , and Fe 7 C 3 were not estimated as proper uncertainty propagation would require knowledge of the covariance matrix relating the fitted parameters V 0 , K T0 , K ′ T0 , 0 , and q. Concerning the stability of these phases in the inner core, Ozawa et al (2011) find B2-FeO to be favored over B1-FeO above 240 GPa at 4000 K, thereby suggesting the B2 phase is stable in the inner core, and ab initio studies by Huang et al (2018) Ahrens and Jeanloz (1987) suggest that cubic pyrite is stable up to 320 GPa. While recent theory suggests that C2/m-FeS 2 may be stable at inner core conditions (Bazhanova et al, 2017), experimental equations of state are also not presently available for this phase.…”
Section: Iron Alloys At Inner Core Conditionsmentioning
confidence: 99%
“…Еще один необычный оксид (Fe x Ni 1-x ) 2 O недавно был предсказан на основании энергетических расчетов как устойчивый в интервале давлений 270-400 ГПа и, соответственно, как возможный компонент ядра Земли (Huang et al, 2018). Его структура изображена на рис.…”
Section: полиморфные модификацииunclassified
“…Structural stability of different phases of Fe 2 O. Different structural phases of Fe 2 O were studied by Weerasinghe et al, and Huang et al using DFT calculations 1,23 . According to Ref.…”
mentioning
confidence: 99%
“…1 Fe 2 O is formed at pressures ∼ 100 GPa. They found that below 180 GPa 1 (212 GPa 23 ) it has the P6 3 /mmc structure. Then it transforms to the P 3m1 phase and finally at 288 GPa 1 (266 GPa 23 ) to the I4/mmm structure.…”
mentioning
confidence: 99%